The Production Mechanism of Single Cell Oil from Aspergillus terreus in a Solid Fermentation System Using a Mixture of Tapioca and Tofu Waste Media - Debby M Sumanti; Carmencita Tjahjadi; Marleen Herudiyanto; Tati Sukarti (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2005)
Fat is an important nutrient for health. Considering the ever-increasing annual demand for cooking oil as a result of the rapid increase in population new sources of poly-unsaturated fats must be searched for. One potential source is the Single Cell Oil (SCO); production of SCO does not require vast areas of land, production time is relatively short and is not affected by enviromental conditions. Moreover, product synthesis and production volume can be easily controlled; Moreover, the tri-acyl-glyceral produced contain essential fatty acids, i.e linoleic and linolenic acid. The objectives of this research was to study the influence of two mold strains of A. terreus and the C/N ratio of the growth medium consisting of cassava atarch and tofu processing waste on SCO production. This research consisted of two parts. The first part was a study on keeping methods of pure cultures of A. terreus, preparation of starter cultures, isolation of mold from the starter culture and preparation of fermentation media. The second part of the research was fermentation of A. terreus strain FNOC 6039 and FNOC 6040 on solid media made of tapioca and tofu waste having C/N ratios of 25/1, 30/1, 35/1, 40/1 and 45/1. Post-fermentation observations on the growth medium slabs consisted of moisture, starch, total sugars and protein content and SCO production. Both strain of A. terreus and C/N ratio affected moisture, starch, total sugars and protein content of the growth media. The A. terreus FNOC 6040 strain growth on a medium with C/N ratio of 45/1 was the most potential oil producer, i.e. 14,63% crude SCO. The oil was brownish yellow in color and has a slightly fishy aroma. Keywords : Single Cell Oil, Solid Fermentation, Casava starch and Tofu Processing Waste, Aspergillus terreus mold strain.